Strategy To Assess Zoonotic Potential Reveals Low Risk Posed by SARS-Related Coronaviruses from Bat and Pangolin - Yang, Yong; Shen, Xu-Rui; Zhang, Yu-Lan; Jiang, Ren-di; Wang, Xi; Guan, Zhen-Qiong; Li, Qian; Yao, Yu-Lin; Gong, Qian-chun; Geng, Rong; Wang, Qi; Zhu, Yan; et al. (mBio, 2023)
Evaluation of the zoonotic risk of animal SARSr-CoVs is important for future disease preparedness. However, there are misconceptions regarding the risk of animal viruses. In the last 2 decades, pathogens originating in animals may have triggered three coronavirus pandemics, including the coronavirus disease 2019 pandemic. Thus, evaluation of the spillover risk of animal severe acute respiratory syndrome (SARS)-related coronavirus (SARSr-CoV) is important in the context of future disease preparedness. However, there is no analytical framework to assess the spillover risk of SARSr-CoVs, which cannot be determined by sequence analysis alone. Here, we established an integrity framework to evaluate the spillover risk of an animal SARSr-CoV by testing how viruses break through key human immune barriers, including viral cell tropism, replication dynamics, interferon signaling, inflammation, and adaptive immune barriers, using human ex vivo lung tissues, human airway and nasal organoids, and human lung cells. Using this framework, we showed that the two pre-emergent animal SARSr-CoVs, bat BtCoV-WIV1 and pangolin PCoV-GX, shared similar cell tropism but exhibited less replicative fitness in the human nasal cavity or airway than did SARS-CoV-2. Furthermore, these viruses triggered fewer proinflammatory responses and less cell death, yet showed interferon antagonist activity and the ability to partially escape adaptive immune barriers to SARS-CoV-2. Collectively, these animal viruses did not fully adapt to spread or cause severe diseases, thus causing successful zoonoses in humans. We believe that this experimental framework provides a path to identifying animal coronaviruses with the potential to cause future zoonoses. IMPORTANCE Evaluation of the zoonotic risk of animal SARSr-CoVs is important for future disease preparedness. However, there are misconceptions regarding the risk of animal viruses. For example, an animal SARSr-CoV could readily infect humans. Alternately, human receptor usage may result in spillover risk. Here, we established an analytical framework to assess the zoonotic risk of SARSr-CoV by testing a series of virus-host interaction profiles. Our data showed that the pre-emergent bat BtCoV-WIV1 and pangolin PCoV-GX were less adapted to humans than SARS-CoV-2 was, suggesting that it may be extremely rare for animal SARSr-CoVs to break all bottlenecks and cause successful zoonoses.